ChemInform Abstract: Oxamato‐Based Coordination Polymers: Recent Advances in Multifunctional Magnetic Materials. Issue 35 (2nd September 2014) - Grancha, Thais; Ferrando‐Soria, Jesus; Castellano, Maria; Julve, Miguel; Pasan, Jorge; Armentano, Donatella; Pardo, Emilio
Abstract Review: [47 refs.